2015
DOI: 10.1667/rr13927.1
|View full text |Cite
|
Sign up to set email alerts
|

Serum Amyloid A as a Biomarker for Radiation Exposure

Abstract: There is a need for minimally invasive biomarkers that can accurately and quickly quantify radiation exposure. Radiation-responsive proteins have applications in clinical medicine and for mass population screenings after a nuclear or radiological incident where the level of radiation exposure and exposure pattern complicate medical triage for first responders. In this study, we evaluated the efficacy of the acute phase protein serum amyloid A (SAA) as a biomarker for radiation exposure using plasma from irradi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
35
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(36 citation statements)
references
References 42 publications
0
35
1
Order By: Relevance
“…FL is a cytokine known to induce proliferation and differentiation of bone marrow stem cells of myeloid and lymphoid origin and has recently been described as a biomarker of radiation exposure (3). The apolipoprotein SAA is a major acute phase reactant protein playing a central role in the inflammatory response and has been characterized as a marker of radiation exposure in heterogeneous radiation exposure profiles (46). MMP9 is active in extra-cellular matrix (ECM) degradation and FGB, the principle protein involved in clot formation, were also included in the study having been previously shown to be radiation responsive (4).…”
Section: Introductionmentioning
confidence: 99%
“…FL is a cytokine known to induce proliferation and differentiation of bone marrow stem cells of myeloid and lymphoid origin and has recently been described as a biomarker of radiation exposure (3). The apolipoprotein SAA is a major acute phase reactant protein playing a central role in the inflammatory response and has been characterized as a marker of radiation exposure in heterogeneous radiation exposure profiles (46). MMP9 is active in extra-cellular matrix (ECM) degradation and FGB, the principle protein involved in clot formation, were also included in the study having been previously shown to be radiation responsive (4).…”
Section: Introductionmentioning
confidence: 99%
“…Partial-body exposures have also been shown to correlate with plasma expression of SAA, FL and G-CSF using a murine model ( 34 , 35 ). These studies were able to show relative increases in expression of plasma biomarkers correlating to an increasing area of partial-body exposure ( 26 , 36 ).…”
Section: Proteomicsmentioning
confidence: 93%
“…The relationship between radiation injury and activation of the acute-phase response is also well established with correlations between CRP elevation and onset and severity of acute radiation syndrome (ARS) ( 4 ). Elevation of acute-phase proteins such as CRP and serum amyloid A (SAA) were also reported to increase in a dose-dependent manner after irradiation ( 25 , 26 ).…”
Section: Proteomicsmentioning
confidence: 99%
“…Frequency of occurrence of cells with dumbbell-shaped nuclei depends on the dose of irradiation and this correlation is described by a linearquadratic function with the following equation: y = 0.003+0.014x +0.005x 2 [31]. We would like to emphasize that the simplest biomarkers (nuclei abnormalities) we suggest for radiation exposure detection in vivo is not an alternative to classical radiation biomarkers in vitro [17], as well as to other modern approaches [2][3][4][5][44][45][46]. Detection of chromosomal aberrations (dicentrics) and the cytochalasine B micronucleus and "Cytome" methods are reliable bioindication and biodosimetry methods.…”
Section: Dumbbell-shaped Nucleimentioning
confidence: 99%
“…The field of activity of biodosimetry has significantly expanded with the methods of genomics [1,2], proteomics [3,4], metabolomics [5] and transcriptomics [6]. At the same time, methods of cytogenetics that require the cultivation of lymphocytes in vitro or the use of special equipment still remain the classical methods [7][8][9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%